Penguatan Sistem Pendidikan Pondok Pesantren Mu’adalah di Era Globalisasi (Studi Kasus Pondok Pesantren Modern Baitul Arqom Balung Kabupaten Jember) - Siti Nursyamsiyah (Universitas Muhammadiyah Jember, 2019)
In an attempt to strengthen inherent values in this era of development and globalization, Mu’adalah Islamic boarding school is always struggling to maintain its identity by being open to systems which come from outside influence. By providing reinforcements in its educational system, Islamic boarding school has successfully maintained its existence over time. This is usually characterized by both shifts and changes that take place in line with current ages. There are two aspects that undelie the success of the performance of Mu’adalah Islamic boarding school: First, its legal status, by which it refers to the state whereby Islamic boarding schools are able to maintain their legal status every four year. Second, the quality of its graduates, by which it refers to the condition where the graduates of certain Islamic boarding schools conform with the standards set by the internal organization as well as those derived from the demands of more general community. In general, all of these are done on the basis of three renewals, namely: the curriculum, methodology and by optimizing Islamic boarding school as a community development center.